1982
DOI: 10.1136/thx.37.6.417
|View full text |Cite
|
Sign up to set email alerts
|

Immediate response to cigarette smoke.

Abstract: Using an automated method of calculating airways resistance in the body plethysmograph, we have investigated changes occurring immediately after inhalation of cigarette smoke. Decreases in specific conductance occurred by the time of the first measurement seven or eight seconds after exposure to single inhalations of cigarette smoke in 12 smokers and 12 nonsmokers. Less than half of the initial change was present 40 seconds after the inhalation. Initial responses were greater in the non-smokers. Responses recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Even in teenagers who have smoked for only a few years, maximum expiratory flow-volume curves demonstrate decreases in flow rates at small lung volumes [5]. The effect of acute smoking on airway calibre was also documented by Ress et al [6]. The obstruction to airflow that develops in 15 to 20% of heavy smokers is thought to be due to abnormalities in airways with less than 2 mm internal diameter [7].…”
Section: Introductionmentioning
confidence: 76%
“…Even in teenagers who have smoked for only a few years, maximum expiratory flow-volume curves demonstrate decreases in flow rates at small lung volumes [5]. The effect of acute smoking on airway calibre was also documented by Ress et al [6]. The obstruction to airflow that develops in 15 to 20% of heavy smokers is thought to be due to abnormalities in airways with less than 2 mm internal diameter [7].…”
Section: Introductionmentioning
confidence: 76%
“…Rees et al [18] found that treat ment with salbutamol decreased the effect of smoke on specific conductance. Nadel and Comroe [19] found that isuprel diminished the constrictive re sponse to smoke, while Sterling and Chir [20] found that atropine abolished its response.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inhalation of smoke from even a single cigarette has been shown to cause brief broncho-constriction in both smokers and non-smokers 11 . The reduction in specific conductance of the airways as the acute effect of smoking has been reported to be within 8 seconds after starting smoking, whereas the maximum acute effect 30 minutes after smoking 15 . Smoking of tobacco significantly reduces the cardio-respiratory functions 16,17 .…”
Section: Introductionmentioning
confidence: 99%